Mean streets : migration, xenophobia and informality in South Africa - Crush, Jonathan, 1953-; Chikanda, Abel; Skinner, Caroline (The Southern African Migration Programme (SAMP) : The African Centre for Cities : The International Development Research Centre, 2015)
"This book powerfully demonstrates that some of the most resourceful entrepreneurs in the South African informal economy are migrants and refugees. Yet far from being lauded, they take their life into their hands when they trade on South Africa's 'mean streets'. The book draws attention to what they bring to their adopted country through research into previously unexamined areas of migrant entrepreneurship. Ranging from studies of how migrants have created agglomeration economies in Jeppe and Ivory Park in Johannesburg, to guanxi networks of Chinese entrepreneurs, to competition and cooperation among Somali shop owners, to cross-border informal traders, to the informal transport operators between South Africa and Zimbabwe, the chapters in this book reveal the positive economic contributions of migrants. these include generating employment, paying rents, providing cheaper goods to poor consumers, and supporting formal sector wholesalers and retailers. As well, Mean Streets highlights the xenophobic responses to migrant and refugee entrepreneurs and the challenges they face in running a successful business on the street"--Provided by publisher
Keywords: Immigrants -- South Africa -- Economic conditions.; Xenophobia -- South Africa.; Street vendors -- South Africa.; Peddlers -- South Africa.; Informal sector (Economics) -- South Africa.; Entrepreneurship -- South Africa.; Xénophobie -- Afrique du Sud.; Vendeurs de rue -- Afrique du Sud.; Colporteurs -- Afrique du Sud.; Secteur informel (Économie politique) -- Afrique du Sud.; Entrepreneuriat -- Afrique du Sud.; "Museum, historic sites, gallery & art guides."; SOCIAL SCIENCE -- Emigration & Immigration.; Entrepreneurship; Immigrants -- Economic conditions; Informal sector (Economics); Peddlers; Street vendors; Xenophobia; South Africa